2023
DOI: 10.1002/adhm.202302374
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic Approach of Antibody‐Photosensitizer Conjugate Independent of KRAS‐Mutation and Its Downstream Blockade Pathway in Colorectal Cancer

Minji Ahn,
Taebum Lee,
Kyoung Sub Kim
et al.

Abstract: Here, we present a novel approach to improve the efficacy of antibody‐drug conjugates (ADC) by integrating antibody‐mediated immunotherapy and photodynamic therapy (PDT) in a combination therapy system utilizing an antibody‐photosensitizer conjugate (APC) platform based on a poloxamer polymer linker. To specifically target KRAS‐mutated cancer cells, we synthesized an antibody anti‐epidermal growth factor receptor (EGFR), cetuximab, with a poloxamer linker coupled with the photosensitizer chlorin e6 (MPXC) thro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…Over the past several decades, clinical practice and exploratory studies have demonstrated that a singular treatment modality is ineffective in combating refractory diseases, such as cancer, diabetes, arthritis, and multiple sclerosis, due to its complexity, heterogeneity, and drug resistance. In line with therapeutic advancements, combination therapies have emerged as a superior approach to overcome monotherapy limitations. , Combination therapy, achieved by concurrently administering multiple drugs or integrating diverse therapeutic modalities, can enhance therapeutic effectiveness, minimize side effects, combat drug resistance, and mitigate the chances of recurrence. ,, For example, the highly active antiretroviral therapy, which involves the combination of three or more anti-HIV drugs, has become the predominant therapeutic approach for acquired immune deficiency syndrome. , Moreover, the World Health Organization recommends artemisinin combination therapy as the primary treatment for malaria patients . Significantly, the growing acknowledgment of the distinct benefits of combination therapy over monotherapy in treating various diseases has fostered its gradual adoption in clinical settings.…”
Section: Introductionmentioning
confidence: 99%
“…Over the past several decades, clinical practice and exploratory studies have demonstrated that a singular treatment modality is ineffective in combating refractory diseases, such as cancer, diabetes, arthritis, and multiple sclerosis, due to its complexity, heterogeneity, and drug resistance. In line with therapeutic advancements, combination therapies have emerged as a superior approach to overcome monotherapy limitations. , Combination therapy, achieved by concurrently administering multiple drugs or integrating diverse therapeutic modalities, can enhance therapeutic effectiveness, minimize side effects, combat drug resistance, and mitigate the chances of recurrence. ,, For example, the highly active antiretroviral therapy, which involves the combination of three or more anti-HIV drugs, has become the predominant therapeutic approach for acquired immune deficiency syndrome. , Moreover, the World Health Organization recommends artemisinin combination therapy as the primary treatment for malaria patients . Significantly, the growing acknowledgment of the distinct benefits of combination therapy over monotherapy in treating various diseases has fostered its gradual adoption in clinical settings.…”
Section: Introductionmentioning
confidence: 99%
“…The intrinsic scarcity of tumor antigens led to poor tumor recognition and cytotoxicity of T cells. Recently, radiotherapy [ 18 , 19 ], chemotherapy [ 20 , 21 ], and phototherapy [ [22] , [23] , [24] , [25] ] have been reported to promote tumor antigen exposure in TME, thus improving the immunogenicity of ISV. Among them, photothermal therapy (PTT) has emerged as a novel ISV paradigm due to its high selectivity, low systemic toxicity, and limited therapeutic resistance [ [26] , [27] , [28] , [29] ].…”
Section: Introductionmentioning
confidence: 99%